IMPLEMENTASI THINK, TALK, WRITE (TTW) DENGAN KARTU “CERITA DALAM GENGGAMAN” UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA KELAS IV - Prasetyanti, Yulia Wulan; Untarti, Reni; Astuti, Sri Rahayu Puji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This Classroom Action Research was designed to improve the literacy skills of fourth-grade students at SD Negeri 2 Purwokerto Lor through the application of the Think, Talk, Write (TTW) Cooperative Learning model, supported by